THE EFFECT OF THE SSCS LEARNING MODEL ASSISTED BY ANIMATED VIDEOS ON JUNIOR HIGH SCHOOL STUDENTS' LEARNING OUTCOMES - Anggela Silvia; Khairil Arif; Tuti Lestari (Universe, 2026)
Students' low learning outcomes in science are often associated with the use of monotonous instructional models, limited learning media, and insufficient student engagement, which reduce students' understanding of scientific concepts. The Search, Solve, Create, and Share (SSCS) learning model, supported by animated videos, offers a student-centered instructional approach that may enhance learning outcomes. This study aimed to examine the effect of the SSCS learning model assisted by animated videos on junior high school students' learning outcomes in the topic of the human excretory system. A quasi-experimental research design employing a nonequivalent control group design was used. The participants were selected through purposive sampling, with one class assigned as the experimental group and another as the control group. Data were collected using a validated multiple-choice test administered as both a pretest and a posttest. The data were analyzed using an independent-samples t-test. The results showed that the experimental group achieved a higher mean posttest score (84.50) than the control group (63.00). Furthermore, the hypothesis test revealed a statistically significant difference between the two groups (p = 0.019 < 0.05), indicating that the SSCS learning model assisted by animated videos significantly improved students' learning outcomes. Therefore, integrating the SSCS learning model with animated video media can be considered an effective instructional strategy for improving junior high school students' science learning outcomes.